HIV, Tuberculosis, Diabetes Mellitus and Hypertension Admissions and Premature Mortality among Adults in Uganda from 2011 to 2019: is the Tide Turning? - Kazibwe, Andrew; Bisaso, Kuteesa Ronald; Kyazze, Andrew Peter; Ninsiima, Sandra; Ssekamatte, Phillip; Bongomin, Felix; Baluku, Joseph Baruch; Kibirige, Davis; Akabwai, George Patrick; Kamya, Moses R.; Mayanja‑Kizza, Harriet; Kagimu, Magid; et al. (Tropical Medicine and Health, 2022)
The growing burden of diabetes mellitus (DM) and hypertension (HTN) on the background of endemic Human Immuno-deficiency Virus (HIV) and tuberculosis (TB) is a concern in low- and middle-income countries. We aimed to describe annual trends in admissions, mortality rates and premature mortality (years of potential life lost—YPLLs) due to HIV, tuberculosis (TB), diabetes mellitus (DM) and hypertension (HTN) in Uganda. We conducted a retrospective cohort study, retrieving electronic records of adults admitted to Mulago and Kiruddu national referral hospitals medical wards between 1st January 2011 and 31st December 2019. We used STATA BE 17.0 and GraphPad Prism 8.0.2 to compute total admissions, inpatient crude mortality rates, and YPLLs; and demonstrate trends using Mann–Kendall test. Of 108,357 admissions, 55,620 (51.3%) were female, 15,300 (14.1%) were recorded in 2012, and 22,997 (21.2%) were aged 21–30 years. HIV, TB, DM and HTN accounted for 26,021 (24.0%); 9537 (8.8%); 13,708 (12.7) and 13,252 (12.2%) of all admissions, respectively. Overall inpatient mortality was 16.7% (18,099/108,357), 53.5% (9674/18,099) were male, 21.5% (3898) were aged 31–40 years and 2597 (14.4%) were registered in 2013. HIV, TB, DM and HTN accounted for 35.6% (6444), 14.6% (2646), 9.1% (1648) and 11.8% (2142) of all deaths, respectively. Total admissions (Kendall’s tau-B = − 0.833, p < 0.001) and deaths declined (Kendall’s tau-B = − 0.611, p = 0.029). A total of 355,514 (mean = 20.8 years, SD 30.0) YPLLs were recorded, of which 54.6% (191,869) were in males; 36.2% (128,755) were among those aged 21–30 years and were recorded in 2012 (54,717; 15.4%). HIV, TB, DM and HTN accounted for 46.5% (165,352); 19.5% (69,347); 4.8% (16,991) and 4.5% (16,167) of YPLLs, respectively. Proportionate contribution of HIV to deaths and YPLLs declined, remained stagnant for TB; and increased for both DM and HTN. TB and HIV account for higher though declining, while DM and HTN account for lower albeit rising morbidity and premature mortality among adult medical patients in Uganda. TB prevention and treatment; and DM/HTN service integration in HIV care should be optimized and scaled up.
Keywords: Trend, Premature mortality, Inpatient, HIV, Tuberculosis, Diabetes mellitus, Hypertension, Uganda